2019
DOI: 10.3390/molecules24193628
|View full text |Cite
|
Sign up to set email alerts
|

Two New AChE Inhibitors Isolated from Li Folk Herb Heilaohu “Kadsura coccinea” Stems

Abstract: Two new triterpenoids, named kadsuricoccins A and B, together with three known ones, were isolated from the Li folk herb Heilaohu, the stems of Kadsura coccinea (Lem.) A. C. Smith, which was used for food and as a healthy supplement. Their structures were elucidated by comprehensive analyses of mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopic data. To search healthy components, an acetylcholinesterase (AChE) inhibitory activity test by Ellman’s Method was conducted, kadsuricoccins A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Kadsura coccinea (KC) has also gained interest in Chinese folk medicine to identify effective treatments for preventing several diseases [ 1 , 2 ]. It is not only consumed as food but also is highly regarded for its pharmacological properties, especially anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory, and anti-tumor properties [ 3 , 4 ]. Many studies have shown the therapeutic effects of KC such as in treating gastrointestinal disorders and rheumatoid arthritis, calming the heart, strengthening the kidneys, and promoting blood and fluid circulation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kadsura coccinea (KC) has also gained interest in Chinese folk medicine to identify effective treatments for preventing several diseases [ 1 , 2 ]. It is not only consumed as food but also is highly regarded for its pharmacological properties, especially anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory, and anti-tumor properties [ 3 , 4 ]. Many studies have shown the therapeutic effects of KC such as in treating gastrointestinal disorders and rheumatoid arthritis, calming the heart, strengthening the kidneys, and promoting blood and fluid circulation [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lignans [ 2 , 3 , 4 , 5 , 6 ] and triterpenoids [ 7 , 8 , 9 , 10 , 11 , 12 ] from this plant have been received considerable attention. In previous studies, the compounds of K. coccinea have been reported with various activities, including the inhibition of nitric oxide production [ 2 , 13 ], antioxidant [ 14 , 15 ], anti-HIV [ 16 ], anti-inflammatory [ 17 ], hepatoprotective [ 18 ], acetylcholinesterase and butyrylcholinesterase inhibitory activities [ 15 , 19 , 20 ], and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the properties of photoprotection and melanogenesis, several cosmetic and pharmaceutical candidates with antioxidant, photoprotective and anti-melanogenic effects have been investigated (31,36,37). Dibenzocyclooctadiene lignans are one of the most widely used biologically active compounds extracted from Kadsura medicinal plants in China and other Asian countries (2,38). Studies have confirmed that Kadsura medicinal plants exert various pharmacological effects, including anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory and antitumor properties, and are widely used in the treatment of rheumatoid arthritis and promoting blood and fluid circulation (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%